2014
DOI: 10.1007/s40609-014-0022-9
|View full text |Cite
|
Sign up to set email alerts
|

‘At school I got myself a certificate’: HIV/AIDS Orphanhood and Secondary Education: a Qualitative Study of Risk and Protective Factors

Abstract: Secondary school is a period during which risk of school dropout is highest. To date, little research has examined reasons for school dropout amongst HIV/ AIDS-orphaned children, who are affected economically, psychosocially and educationally. HIV/AIDS orphanhood can perpetuate poverty and increase school dropout in a range of ways, including inability to pay school fees, family disruption and stigma. Related research mostly focuses on school performance and completion and, more recently, on context-specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Orphaned and vulnerable children in sub-Saharan Africa experience multiple barriers to their education and well-being, including poverty, neglect, young caregiving and unfriendly school environments (Campbell et al 2014;Evans, 2012a;Skovdal 2008;Watkins et al 2014). Girls and young women are particularly disenfranchised.…”
Section: Schools As Spaces Of Care and Support?mentioning
confidence: 99%
See 1 more Smart Citation
“…Orphaned and vulnerable children in sub-Saharan Africa experience multiple barriers to their education and well-being, including poverty, neglect, young caregiving and unfriendly school environments (Campbell et al 2014;Evans, 2012a;Skovdal 2008;Watkins et al 2014). Girls and young women are particularly disenfranchised.…”
Section: Schools As Spaces Of Care and Support?mentioning
confidence: 99%
“…Struggles faced by orphaned and vulnerable pupils Primary and secondary school teachers reported that orphaned and vulnerable pupils came to school with empty stomachs and worried about their home situation, which affected their concentration in class. Echoing previous research from South Africa(Cluver et al 2012;Watkins et al 2014), Zambia(Day and Evans 2015), Tanzania and Uganda (Evans 2012a), young people with caring responsibilities experienced difficulties in arriving at school on time and in concentrating as well as in meeting the costs of school uniforms and materials. They often missed classes due to their caring responsibilities or their own illness for periods of a few days up to several months or dropped out of school permanently.…”
mentioning
confidence: 90%
“…free schooling, school‐books and school meals) is associated with lower externalizing mental health distress and modifies the risk pathway from ACEs to internalizing mental health distress. This could operate through a number of mechanisms which need to be further explored: for instance, adolescent girls who receive free schooling may experience lower mental health distress because they do not have the additional worry of being able to pay the school fees . In addition, by receiving free schooling social protection, adolescent girls receive one hot meal a day which may prevent hunger and thus reduce risk for mental health distress .…”
Section: Discussionmentioning
confidence: 94%
“…For children in low‐resource settings and affected by HIV, paying school fees can be a substantial strain on households, causing school dropout and uncertainty regarding education. Qualitative work identifies that this is a source of distress for children . Recent research evidence suggests that school non‐attendance is linked to higher HIV risk behaviour in multiple contexts while school attendance and increases in education levels have been shown to significantly reduce HIV acquisition and prevalence .…”
Section: Introductionmentioning
confidence: 99%
“…There is consistent evidence that poverty is associated with poor educational outcomes (Battin-Pearson et al, 2000;van der Berg, 2005). Specifically, in South Africa poverty has been associated with elevated risk of school dropout and grade failure (Fleisch, Shindler, & Perry, 2012;Flisher, Townsend, Chikobvu, Lombard, & King, 2010;Orkin, Boyes, Cluver, & Zhang, 2014;Watkins, Sello, Cluver, Kaplan, & Boyes, 2014). It has been argued that the inability to afford school necessities (e.g.…”
Section: Poverty and Educationmentioning
confidence: 99%